An Analysis of Individual, Parental, and Family Determinants of Gifted Placement among Children of Immigrants – Evidence from the 2014 SIPP Data. - Pham, Trang; Altman, Claire E. (Journal of Child & Family Studies, 2024)
This study provided an innovative analysis of placement into gifted educational programs among children of immigrants. Leveraging the immigration module of the 2014 Survey of Income and Program Participation (SIPP), we constructed a novel measure of parents' nativity and immigration statuses. Connecting research on gifted education and immigration, our study examined factors associated with the gifted placement of children of immigrants, such as a child's demographics, parental and family characteristics, and, most notably, parents' nativity and immigration statuses. We found disproportionate representation of children of immigrants in gifted and talented programs, whereby children from families with higher-than-average incomes, White and Asian children, were overrepresented, and Hispanic children were underrepresented. Our findings also showed that children in families with two foreign-born parents had lower odds of gifted placement than children of one foreign-born and one US-born parent (mixed-nativity parents). Among the two foreign-born parent families, we found variations in children's gifted placement across different parental immigration status compositions, specifically between those with two naturalized parents versus other children of immigrants. Moreover, our gender heterogeneity test showed that girls have higher odds of gifted placement than boys, which was opposite to what was previously known in the gifted education literature and suggests differential parental attention on children's education in immigrant families. Highlights: This study explored various individual, parental, and family factors associated with gifted placement among children of immigrants. The novel contribution of this study was to test whether parents' nativity and immigration status predicted a child's gifted placement. Our findings suggest that parents' nativity and immigration statuses were significantly associated with a child's gifted placement, in which children of mixed-nativity couples (one foreign-born and one U.S.-born parent) were most likely to be placed in a gifted program. We also confirmed the existence of the "disproportional representation" in gifted programs among children of immigrants. Other determinants of gifted placement among children of immigrants included the child's age and gender, the parents' years of education, and the number of children in the family. Our extended analyses also uncovered complicated relationships between these determinants and the child's gifted placement. Educational policymakers are encouraged to be aware of the diverse family backgrounds of children of immigrants when making decisions on gifted identification and curricula to be inclusive of this small yet increasing school-aged population.